2017
DOI: 10.1139/cjas-2016-0219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grain Source and Dried Corn Distillers Grains Plus Solubles Oil Concentration on Finishing Cattle Performance and Feeding Behavior

Abstract: Eighty-one steers [428 ± 3.5 kg of body weight (BW)] were used to determine the effect of grain type (corn vs. barley) and oil concentration of dried corn distillers grains plus solubles (DDGS; moderate = 7.9% vs. low = 4.5% ether extract) on growth performance, feeding behavior, and carcass characteristics. Intake and feeding behavior traits were calculated from data generated via the Insentec feeding system. Steers were slaughtered with an average BW of 668 ± 4.4 kg. Final BW and average daily gain (ADG) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…However, the lack of a response in ruminal VFA concentrations may indicate minimal effects on energy supply from ruminal fermentation between steers fed diets containing DDGS with differing oil concentration. This is further supported from results from our companion study indicating no differences in growth performance in steers fed diets containing DDGS with differing oil concentration (Rodenhuis et al 2017).…”
Section: Discussionsupporting
confidence: 73%
“…However, the lack of a response in ruminal VFA concentrations may indicate minimal effects on energy supply from ruminal fermentation between steers fed diets containing DDGS with differing oil concentration. This is further supported from results from our companion study indicating no differences in growth performance in steers fed diets containing DDGS with differing oil concentration (Rodenhuis et al 2017).…”
Section: Discussionsupporting
confidence: 73%
“…These results are likely due to increased energy supply as no differences were observed in microbial or total CP flow to the duodenum. This theory is supported by results from a companion growth performance study (Rodenhuis et al 2017) utilizing the same diets with the results showing that steers fed diets containing barley had decreased DMI with the same ADG, resulting in improved gain to feed ratio.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, in the present study there was an increase in lipid intake in the moderate-vs. low-oil DDGS but no differences were found in fecal lipid output, which indicates that the animal is utilizing more of the lipids from the moderateoil DDGS than the low-oil DDGS, which supports the theory that the lipids in the lower oil concentration products may not be as digestible. This theory needs to be studied further to know the full effects and implications that can be associated with feeding an ethanol coproduct with lower oil concentrations, especially as in the companion study (Rodenhuis et al 2017), feeding the same diets, there were no observed differences in growth performance or carcass characteristics between steers fed diets containing low-oil DDGS vs. moderateoil DDGS. It should be pointed out that NDF and ADF concentrations were greater and starch concentrations lesser in the moderate-oil than the low-oil DDGS which could potentially influence the responses observed in this experiment.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, alterations in the rate of DMI and time eating by steers supplemented with RAC could potentially influence rumen fermentation and result in decreased ruminal pH ( Gonzalez et al, 2012 ). Although visual signs of acidosis were not observed in steers from either treatment, changes in forage source and level ( Swanson et al, 2017 ), grain source ( Rodenhuis et al, 2017 ) and processing ( Swanson et al, 2014 ), time of feeding ( Prezotto et al, 2017 ), and feed additive inclusion ( Swanson et al, 2018 ) can potentially alter effects and interactions with RAC.…”
Section: Discussionmentioning
confidence: 99%